Semantic properties of Russian proverbs with the notion “man” - Kambarova, Marzhan Adil qizi (The Lingua Spectrum, 2026)
The article examines the semantic aspects of the lexeme “human” in Russian proverbs and analyzes its role in shaping the semantic content of paremiological units. It also identifies the main meanings and evaluative characteristics associated with the image of a human in the folk linguistic worldview. Special attention is paid to reflecting the moral, social, and behavioral qualities of a person embedded in the proverb corpus of the Russian language. The study identifies typical semantic groups of the lexeme “human” and its role in expressing generalized life observations and value orientations. The research material included dictionaries, notably V.I. Dal’s “Proverbs and Sayings of the Russian people” along with other lexicographical sources. Analysis shows that the concept of “human” is represented not only by the lexeme “human” itself but also by a wide range of words denoting gender, age, familial relations, social belonging, and quantitative characteristics. The study highlights key semantic models: human and his image, human and his soul, human and society, human’s positive and negative qualities, and others. The results contribute to a deeper understanding of Russian proverbs and the representation of the concept of “human” in national culture.